Happy Feet: The Essential Guide - Dakin, Glenn (New York DK Books, 2006)
Join Mumble on his search for his Heartsong and discover why the Emperor penguin colony is going hungry.
K - 2
Keywords: 1. Happy Feet (Motion picture); 2. Penguins